Separation of α-, β-, γ-, δ-tocopherols and α-tocopherol acetate on a pentaerythritol diacrylate monostearate-ethylene dimethacrylate monolith by capillary electrochromatography - Patcharin Chaisuwan (2018)
This work reports the first use of a monolith with method development for the separation of tocopherol (TOH) compounds by CEC with UV detection. A pentaerythritol diacrylate monostearate-ethylene dimethacrylate (PEDAS-EDMA) monolithic column has been investigated for an optimised condition to separate α, β, γ- and δ-TOHs, and α-tocopherol acetate (TAc). The PEDAS-EDMA monolith showed a remarkably good selectivity for separation of the TOH isomers including the β- and γ-isomers which are not easily separated by standard C8 or C18 particle-packed columns. Retention studies indicated that an RP mechanism was involved in the separation on the PEDAS-EDMA column, but polar interactions with the underlying ester and hydroxyl groups enhanced the separation of the problematic β and γ-isomers. Separation of all the compounds was achieved within 25 min using 3:10:87 v/v/v 100 mM Tris buffer (pH 9.3)/methanol/ACN as the mobile phase. The method was successfully applied to a pharmaceutical sample with recoveries from 93 to 99%. Intraday and interday precisions (%RSD) for peak area and retention time were less than 2.3. LODs for all four TOHs and TAc were below 1 ppm. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.